Genetic and pathogenic characterizations of a naturally occurring reassortant and homologous recombinant strain of the classical infectious bursal disease virus re-emerging in chickens in southern China - Wang, Weiwei; Shi, Jun; Zhang, Yan; Qiao, Yuanzheng; Zuo, Wenbo; Wang, Zhiyuan; Nong, Tingbin; Hu, Shichen; Chen, Yang; Kong, Ruiyang; He, Xiumiao; Wei, Ping (Frontiers in Microbiology, 2023)
Highlights 1. A naturally occurring reassortant and recombinant classical strain GXYL211225 (genotype A1aB1a) was isolated and characterized for the first time. 2. Segment A of GXYL211225 is a result of recombination between the classical strains 150127-0.2 (major parent) and Faragher52-70 (minor parent), and with segment B reasserting with the attenuated vaccine strain. 3. GXYL211225 exhibits an extensive cell-tropism and has been confirmed to be a naturally occurring cell-adapted strain. 4. The virulence of GXYL211225 was intermediate between that of the vvIBDV NN1172 and nvIBDV QZ191002, causing a 10% mortality rate and severe immune organ damages in chickens.